The cassava seed system in Nigeria: Opportunities and challenges for policy and regulatory reform - Wossen, T.; Spielman, David J.; Abdoulaye, Tahirou; Kumar, P. Lava (International Potato Center, 2020)
In many African countries south of the Sahara, farmers depend on the cultivation of vegetatively propagated crops (VPCs) for both consumption and commercial purposes. Yet yields for these crops remain at low levels due, in part, to seed market imperfections that constrain farmers' access to improved varieties and high-quality planting material. Efforts to improve the quality of planting material exchanged in markets or through other channels are often hampered by the unique biological and economic characteristics of vegetative propagation—characteristics that distinguish VPCs from the major cereal crops that drive and shape the policy and investment choices made in many of these countries. This suggests that continued investment in new technologies and systems to produce, package, and distribute VPC planting materials will require customized policies and policy support if these systems are to supply farmers with quality planting material at any significant and sustained scale. This paper explores these issues in the context of the cassava seed system in Nigeria by drawing on (1) prior research, public policy documents, and government statistics; (2) key informant interviews and focus group discussions with seed system actors; and (3) a unique dataset from the 2015 Cassava Monitoring Survey of Nigeria (CMS). The paper examines the production and supply of cassava planting material, the influence of various quality assurance systems on production and supply, and the implications for smallholder farmers in Nigeria. We describe the market, non-market, and regulatory systems that shape the cassava seed market in Nigeria, focusing on effectiveness, influence, and reach. We then explore the ground realities—how farmers actually acquire and use cassava planting material—given the (weak) state of markets and regulation. This is followed by a discussion of alternative policy and regulatory approaches to managing and expanding the cassava seed system, emphasizing a more decentralized approach that prioritizes investment in innovative capacity at the community and enterprise levels.